Child Disciplinary Practices versus Child Rights in Zimbabwe: Viewed through Social Work Lenses - Simango, Tapiwa; Mafa, Itai (Lodz University, 2022)
Although parents are a vital cog in instilling and maintaining child discipline, very little information exists about the methods they employ. Using a qualitative approach, this paper explored the methods used by parents in Zimbabwe—an African context—to discipline children, elucidating their implications on children’s rights. The findings show that parents in Zimbabwe use both violent and non-violent disciplinary methods such as verbal reprimand, beating, and spanking, which, at times, violates children’s rights in the process. The use of non-violent means has also depicted a vio- lation of children’s rights through deprivation of food, denial of playtime and shelter. Evident from the findings was, again, the existence of multiple-layered contestations on child discipline within the socio-cultural discourse—the most popularized being the debate on corporal punishment versus child rights violations. Through social work lenses, the paper provides a basis to dispel an anachro- nistic thought, which rationalizes the instrumentalization of punishment to achieve child discipline, underscoring the need for child rights-oriented discipline.